2022
DOI: 10.1111/maps.13922
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial ages of seven meteorite strewn fields and two single unpaired meteorites from the Sultanate of Oman determined using 14C and 10Be

Abstract: Through the investigation of terrestrial ages of meteorites from Oman, we aim to better understand the time scales of meteorite accumulation and erosion in Oman and the meteorite flux in the past. Here, we present 14C and 14C‐10Be terrestrial ages of seven ordinary chondrite strewn fields and two unpaired single meteorites from the Sultanate of Oman. After critical evaluation of multiple data for each strewn field, we propose “best estimate terrestrial ages,” typically based on 14C/10Be. For objects for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…As the JaH 073 fall happened some 18.1 ka ago (Sliz et al., 2022), there is no direct information about the wind situation during fall time. The overall climatic situation at the end of the last ice age, however, was already similar to the present one, except some displacement of the Intertropical Convergence Zone (ITCZ) due to the more extended ice coverage of the northern hemisphere (Fleitmann & Matter, 2009; Preusser et al., 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the JaH 073 fall happened some 18.1 ka ago (Sliz et al., 2022), there is no direct information about the wind situation during fall time. The overall climatic situation at the end of the last ice age, however, was already similar to the present one, except some displacement of the Intertropical Convergence Zone (ITCZ) due to the more extended ice coverage of the northern hemisphere (Fleitmann & Matter, 2009; Preusser et al., 2002).…”
Section: Methodsmentioning
confidence: 99%
“…JaH 073 samples gave a 14 C fall age of 18.1 ± 2.7 ka (Sliz et al., 2022). The meteorite seems not to be saturated in 10 Be, which resulted in the underestimated age of 14.4 ka reported earlier by Gnos et al.…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation, CO 2 extraction, and 14 C measurements followed the procedures recently established in our laboratory by Mészáros et al (2018) and Sliz et al (2019Sliz et al ( , 2022. Briefly, samples were milled and the 125-200 μm grain size fraction was selected.…”
Section: Measurements and Data Reductionmentioning
confidence: 99%
“…For example, the conditions supporting or limiting meteorite preservations differ significantly among the different deserts. While meteorites found in the deserts of the Sultanate of Oman, North Africa, the United States, and Australia have average terrestrial ages in the range 30-50 ka (e.g., Al-Kathiri et al, 2005;Jull, 1993Jull, , 2006Jull, , 2010Sliz et al, 2022), meteorites found in the Atacama Desert or in Antarctica can have terrestrial ages up to millions of years (e.g., Cassidy, 2003;Drouard et al, 2019;Gattacceca et al, 2011). Terrestrial ages are crucial data for comprehending and quantifying the processes involved in weathering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation